2019
DOI: 10.1002/bse.2335
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring effect of transparency: How does government environmental disclosure facilitate corporate environmentalism?

Abstract: Environmental information transparency is a key policy instrument in environmental governance, which has been emphasized in most of the literature. Although a large body of research has focused on its role at the national or industrial level in the developed countries, few studies have extended it to emerging economies and tested its role in the subnational context. In this paper, we have empirically examined how government environmental disclosure shapes corporate environmentalism in the context of China. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 74 publications
(111 reference statements)
0
46
0
Order By: Relevance
“…Environmental accounting, which is sometimes referred to as ‘green accounting’ (Cho and Patten 2013 ; Marissa Matsler 2019 ) or ‘environmental management accounting (Qian et al 2018 ; Asiri et al 2020 ) is an integral part of the accounting frontier since it combines the traditional accounting reporting with ecological reporting (Lu and Li 2020 ; Tzouvanas et al 2020 ). The high rate of pollution has resulted in more studies in this field (G. Li et al 2018 ; Kostka and Zhang 2018 ; Sun et al 2019 ). Green accounting mainly uses currency or other non-monetary units to record information related to natural resources and the environment (Cho and Patten 2013 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental accounting, which is sometimes referred to as ‘green accounting’ (Cho and Patten 2013 ; Marissa Matsler 2019 ) or ‘environmental management accounting (Qian et al 2018 ; Asiri et al 2020 ) is an integral part of the accounting frontier since it combines the traditional accounting reporting with ecological reporting (Lu and Li 2020 ; Tzouvanas et al 2020 ). The high rate of pollution has resulted in more studies in this field (G. Li et al 2018 ; Kostka and Zhang 2018 ; Sun et al 2019 ). Green accounting mainly uses currency or other non-monetary units to record information related to natural resources and the environment (Cho and Patten 2013 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prior studies on environmental compliance have a mixed conclusion. In the study of Sun et al ( 2019 ), the study realized that less than half of the sample companies complied with environmental reporting. On the contrary, Odoemelam and Okafor ( 2018 ) concluded that more than seventy percent (70%) of the sample companies complied with the environmental disclosures.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although the topic of environmental transparency and its possible influence on financial performance has been widely discussed (see Table ), its application to green innovators has been rather unexplored. Environmental information transparency is one of the key elements in the wider area of environmental governance, both at the national and firm level (Sun, Zeng, Chen, Meng, & Jin, ). It also constitutes an intrinsic aspect of business strategy, embracing all organizational processes and components at the same time (Baraibar‐Diez, Odriozola, & Fernández Sánchez, ).…”
Section: Theoretical Background and Hypotheses' Developmentmentioning
confidence: 99%
“…Institutional voids in emerging economies, including weak enforcement of corporate laws and regulations, lack of independent market intermediaries, and absence of effective internal corporate governance arrangement, exacerbate type I agency problem (Young, Peng, Ahlstrom, Bruton, & Jiang, 2008; Yu, Zeng, Meng, Ma, & Sun, 2020). Comparing with managers having more inside information regarding business, shareholders suffer more from difficulties in achieving business information in emerging markets (Cui et al, 2018; Sun, Zeng, Chen, Meng, & Jin, 2019). This may be because there are barely effective institutions (playing monitoring roles), such as investment banks, head hunting firms, and business press, that can offer valuable and diverse information regarding managers to shareholders (Chen, Zeng, Yu, & Xue, 2020; Luo & Chung, 2013).…”
Section: Theoretical Background and Hypothesismentioning
confidence: 99%